Learning Needs Including Preferences and Digital Technologies: A Study of Mature Students in Higher Education in England - Papé, Nick; Mahmud, Ilias; Hasan, Rahaman; Uddin, Nazim (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Interviews with eight students individually returning to higher education later in life evidence a variety of personal drivers, including financial betterment, career advancement, personal amelioration, subject appeal, formal accreditation and network enlargement. Fashioned by earlier practices, professional goals and societal influences, these factors suggest a need for approaches marked by flexibility and digital integration, including platform-based tools, artificial intelligence (AI)-supported systems, cloud functionality and IoT-enabled resources. Prominence falls on wider societal contributions of governance innovation, ecological responsibility, healthcare improvement and commercial educational reform. With mature learners presenting marked expectations and contexts, attention re-focuses on technology-supported environments, climate-conscious content and practice-led teaching. The authors recommend further exploration in areas related to engagement, curriculum relevance and achievement enhancement.